Human-centered AI through employee participation - Haipeter, Thomas; Wannöffel, Manfred; Daus, Jan-Torge; Schaffarczik, Sandra (Frontiers in Artificial Intelligence, 2024)
This paper is about the role of employee participation in the process of AI implementation both from a theoretical and an empirical point of view by looking at a case study of the telecommunication sector from Germany.